The management of acute ischemic stroke - a role for percutaneous intervention? - Abelson, Mark (SA Heart Journal, 2017)
Acute ischemic stroke due to large vessel occlusion is a devastating disease. In the vast majority of cases little is done to reverse the actual cause, and that is to open the occluded artery. This article reviews the current standard management with intravenous thrombolysis and highlights some of its limitations, and the more recent development of mechanical embolectomy for the emergency treatment of ischemic stroke.